Produção de glossário como estratégia de aprendizagem das embriófitas: uma sequência didática no ensino médio - Arnaldo Fonseca Amorim (2022)
Teaching Botany in High School has been seen as challenging to understand, due to the large volume of concepts and terms, thus generating a lack of interest in many students. The growing need for teaching-learning strategies focused on using new educational tools is discussed in this work. We sought more effective ways to reach 21st-century students, especially in the context of Digital Information and Communication Technologies. In this work, we developed a didactic sequence, which helps students to achieve scientific literacy and learn about the groups of plants. The second-year high school students were involved in producing a glossary with important words and expressions for studying the embryophytes. The work was conducted, evaluated, and continuously monitored by the teacher. The importance of studying this topic was introduced to students through readings on the subject, conversation circles, motivation with videos, and parody. The terms included in the glossary and their meanings were evaluated by the teacher regarding their relevance to learning and were corrected. Subsequently, the feedback was made to the students, who inserted and shared the content on a virtual platform created and made available by the teacher. As pedagogical products, we provide a booklet with the didactic sequence for use by teachers and an e-book with the glossary produced; both will be made available electronically for free access.